Crossing borders: Labor market effects of European integration - Hannah Illing (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2023)
This paper studies the labor market effects of out- and in-migration in the context of cross-border commuting. It investigates an EU policy reform that granted Czech citizens full access to the German labor market, resulting in a Czech commuter outflow across the border to Germany. Exploiting the fact that the reform specifically impacted the Czech and German border regions, I use a matched difference-in-differences design to estimate its effects on local labor markets in both countries. Using a novel dataset on Czech regions, I show that municipalities in the Czech border region experienced a decrease in unemployment rates due to the worker outflow, and a corresponding increase in vacancies. For German border municipalities, I find evidence for slower employment growth (long-term) and slower wage growth (short-term), but no displacement effects for incumbent native workers.
Keywords: J61; J15; R23; 330; Out-Migration; In-Migration; Local Labor Markets